Breaking Bad: Supply Chain Disruptions in a Streamlined Agent Based Model - Domenico Delli Gatti; Elisa Grugni (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We explore the macro-financial consequences of the disruption of a supply chain in an agent based framework characterized by two networks, a credit network connecting banks and firms and a production network connecting upstream and down-stream firms. We consider two scenarios. In the first one, because of the lockdown all the upstream firms are forced to cut production. This generates a sizable down-turn during the lockdown due to the indirect effects of the shock (network based financial accelerator). In the second scenario, only those upstream firms located in the “red zone” are forced to contract production. In this case the recession is milder and the recovery begins earlier. Upstream firms hit by the shock, in fact, will be abandoned by their customers who will switch to suppliers who are located outside the red zone. In this way firms endogenously reconstruct (at least in part) the supply chain after the disruption. This is the main determinant of the mitigated impact of the shock in the “red zone” type of lockdown.
Keywords: E17; E44; E70; 330; supply chain disruption; agent based macroeconomic model